2020
DOI: 10.1002/lom3.10402
|View full text |Cite
|
Sign up to set email alerts
|

Automated plankton classification from holographic imagery with deep convolutional neural networks

Abstract: In situ digital inline holography is a technique which can be used to acquire high‐resolution imagery of plankton and examine their spatial and temporal distributions within the water column in a nonintrusive manner. However, for effective expert identification of an organism from digital holographic imagery, it is necessary to apply a computationally expensive numerical reconstruction algorithm. This lengthy process inhibits real‐time monitoring of plankton distributions. Deep learning methods, such as convol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 72 publications
2
36
0
Order By: Relevance
“…Due to its simplicity, DIHM can easily be incorporated into various cell imaging configurations including amplitude and phase images [ 21 ] and to date, numerous studies have used holography to image marine plankton [ 8 , 22 25 ]. There is increasing interest to use its advantages towards automating classification of plankton and particulates from water samples (e.g., [ 26 28 ]). A review of holographic microscopes for aquatic imaging can be found in Nayak et al [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its simplicity, DIHM can easily be incorporated into various cell imaging configurations including amplitude and phase images [ 21 ] and to date, numerous studies have used holography to image marine plankton [ 8 , 22 25 ]. There is increasing interest to use its advantages towards automating classification of plankton and particulates from water samples (e.g., [ 26 28 ]). A review of holographic microscopes for aquatic imaging can be found in Nayak et al [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For near real-time observations, data transmission is one of the main bottlenecks due to the large file sizes; rapid onboard processing to provide simplified data (e.g., organism presence and counts) in a compressed format, instead of transmitting entire images could help alleviate this problem. For this to work, is it key to develop not only fast and efficient automated classification algorithms, but also those feasible to be developed in a light-weight architecture (Guo et al, 2021). Previous and ongoing efforts toward automated classification of detected particles using various machine learning techniques, including convolutional neural networks, still need holograms to be reconstructed and processed (Davies et al, 2015;Bianco et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Previous and ongoing efforts toward automated classification of detected particles using various machine learning techniques, including convolutional neural networks, still need holograms to be reconstructed and processed (Davies et al, 2015;Bianco et al, 2020). Recent work has focused on the application of deep learning techniques to extract features from the interference patterns recorded on the raw holograms (Shao et al, 2020;Guo et al, 2021). Successful translation to in situ applications would help revolutionize the field, as this would enable skipping the holographic reconstruction step, greatly reducing processing times and facilitating near real-time data dissemination.…”
Section: Limitationsmentioning
confidence: 99%
“…3. As in Davies et al (2015), Guo et al (2021), and (Nayak et al 2018), the first processing step is background subtraction. Nonuniform light levels, scratches in the camera Bottom: Raw holograms with interference from optical turbulence.…”
Section: Diffraction Pattern Detection Algorithmmentioning
confidence: 99%
“…Processing schemes that avoid high-resolution reconstruction would enable analysis of larger (e.g., long time series) data sets and data from larger imaging volume DIHMs. Guo et al (2021) addresses the computational cost of hologram reconstruction by employing deep learning to classify particles based on their diffraction patterns in the raw hologram, eliminating the need for reconstruction. When a particle is relatively close to the camera, the diffraction pattern tends to resemble the shape of the target.…”
mentioning
confidence: 99%